A spectacular tumor response of a giant axillary mass treated with SABR in a palliative scenario - Matsuura, Fernando Kojo; Arruda, Gustavo Viani; Neves, Leonardo Vicente Fay; Faustino, Alexandre Ciuffi; Hamamura, Ana Carolina; Danelichen, Anielle Freitas Bendo (Brazilian Journal of Oncology, 2021)
A 67-year-old male patient with a massive left axillary metastasis from an occult primary tumor (OPT) treated by stereotactic ablative radiotherapy (SABR) is presented. The patient had no clinical response to the initial chemotherapy treatment. Then, a SABR with a single fraction of 16Gy was performed. After SABR, a complete response was observed in the imaging exams after 3 months from the procedure. Currently, the patient is found with painfree, without any analgesic drug. The present case illustrates the importance of considering SABR in palliate care, even for a large tumor.
Keywords: Radiotherapy; Cancer; SABR; Oligometastasis.